#TITLE_ALTERNATIVE# - HAPSARI GRISATYA (NIM : 13206034); Dosen Pembimbing I : Ir. Endon Bharata, MT; Dosen Pembi, ANGGITA
In GPR system, we need antenna to transmit and receive the electromagnetic waves which will be radiated through the surface in order to detect an object in it. However there is always a trade-off between resolution and the depth of penetration. The wider bandwidth the better resolution we got, but that also means the shorter penetration. So we have to adjust the antenna design with GPR applications to get a good result. In this final project, an ultra wideband antenna is designed for 1 to 5 GHz GPR application. The Archimedean spiral antenna is proposed with its characteristic as a consideration. It has wide bandwidth and constant input impedance which are needed for GPR antennas. The addition of reflector and absorber material will be discused in order to modify antenna design. That modifications are important to reach the specification required. Balun design, used as an antenna’s feed, is also included in this project research. This kind of balun must have dual functions, not only as a transformator from balanced to unbalanced system but also as an impedance matching circuit. Matching circuit is required because of the difference between antenna’s impedance, which is affected by the medium of propagation, and coaxial’s impedance as a transmission line. The microstrip tapered balun is proposed to meet that requirments. The design process of both antenna and balun is done by 3D simulator software. In these simulations, some parameters are changed in order to get the optimum design. Next process is fabrication. The antenna is printed on 75x75 mm2 Diclad 527 substrate with dielectric constant of 2,5 and thickness of 1,6mm. Then, the measurements are carried out to get antenna’s characteristics. Those characteristic are return loss, VSWR, and ringing level. From the measurement results,, we know that antenna designed is work well (VSWR < 2) in frequency range required, 1-5 GHz, and it has ringing level < -22dB for 1ns exitation pulse.